Atmospheric fate of hydrofluoroolefins, CxF2x+1CHCH2 (x = 1, 2, 3, 4 and 6): Kinetics with Cl atoms and products. (January 2017) - Ballesteros, Bernabé; Jiménez, Elena; Moreno, Alberto; Soto, Amparo; Antiñolo, María; Albaladejo, José
Abstract: Rate coefficients for the gas-phase reactions of Cx F2x+1 CHCH2 (x = 1, 2, 3, 4 and 6) with Cl atoms were determined at (298 ± 2) K and (710 ± 5) Torr of air using a relative rate technique. Two experimental setups with simulation chambers were employed with Fourier Transform Infrared (FTIR) spectroscopy and Gas Chromatography coupled to Mass Spectrometry (GC-MS) as detection techniques. The Cl-rate coefficients obtained were (in 10 −10  cm 3  molecule −1  s −1 ): (0.85 ± 0.11) for CF3 CHCH2, (1.11 ± 0.08) for C2 F5 CHCH2, (1.12 ± 0.18) for C3 F7 CHCH2, (0.97 ± 0.09) for C4 F9 CHCH2, and (0.99 ± 0.08) for C6 F13 CHCH2 . Additionally, the gas-phase products were identified and quantified, when possible, by FTIR spectroscopy or GC-MS. The main reaction product was reported to be Cx F2x+1 C(O)CH2 Cl. The fluorinated species, Cx F2x+1 CHO and Cx F2x+1 C(O)CH2 Cl, were identified. CF3 C(O)CH2 Cl and CF3 CHO were found to be formed with molar yield of (69 ± 5)% and (9 ± 1)%, respectively. The global lifetime of the investigated Cx F2x+1 CHCH2 due to their Cl-reaction is more than 100 days so this route does not compete with the removal by OH radicals. This lifetime is long enough for Cx F2x+1 CHCH2 to be transported to remote areas where they can be degraded. However, at a local scale, in marine regions at dawn the removal of Cx F2x+1 CHCH2 is expected to occur in ca. 1 day. The atmospheric degradation of these hydrofluoroolefins by Cl atoms is not expected to be a source of bioaccumulative perfluorinated carboxylic acids, Cx F2x+1 C(O)OH. Additionally, the UV absorption cross sections of CF3 C(O)CH2 Cl were determined together with the rate coefficient of the OH reaction by an absolute kinetic method at room temperature. Graphical abstract: Image 1 Highlights: Rate coefficients for Cl-reaction with Cx F2x+1 CHCH2 (HFOs) at 298 K are determined. The atmospheric removal of HFOs initiated by Cl compete with OH reactions at dawn. Main reaction product: Cx F2x+1 C(O)CH2 Cl, i.e. reaction mechanism through Cl- addition to the double bond. Product CF3 C(O)CH2 Cl reacts slowly with OH radicals, but UV photolysis is important. Minor products: Cx F2x+1 CHO, Cx F2x+1 CHOHCH2 Cl and CF2 O.